Pseudomonas sp. LMTK32 production in modified media for pelleting seeds of maca (Lepidium meyenii Walp.) - Guerra Lopez, Martin (2018)
Biomass of Pseudomonas sp. LMTK32 was produced from modification of culture media Yeast Extract Mannitol Broth (YEMB) with the aim of increasing the number of viable cells with the ability to promote the germination of maca seeds pelleted with the bacteria and reduce production costs. In the optimization process, the yeast extract and mannitol components of the LMC culture media were replaced by commercial sources of sucrose and glutamate, whose concentrations were determined in flasks by statistical design from Box-Behnken; in addition, the effect of the inoculum percentage on the time of biomass production was determined. Subsequently, it was determined at the bioreactor level that 28.57 h-1 was the adequate value of the volumetric oxygen transfer coefficient (kLa) at 600 rpm, producing 1.28 x 10 11 CFU / mL. In the LMC M1 modified media, using 12.06 g / L-1 of sucrose, 11.50 g / L-1 of sodium glutamate and 10.9% of inoculant obtained 15x108 CFU / mL, increasing in 48% the number of viable cells with respect to the YEMB control treatment (7.8x10 8 CFU / mL). At the in vitro level, the pelleting of maca seeds with Pseudomonas sp. LMTK32 produced in bioreactor and in the modified media M1 favored its germination. From commercial organic substrates, efficient bacterial inoculants can be produced in the development of maca crops, without altering their ability to promote plant growth.